Impacts of Water Stress Severity and Duration on Potato Photosynthetic Activity and Yields - Jacques, Mandela M.; Gumiere, Silvio J.; Gallichand, Jacques; Celicourt, Paul; Gumiere, Thiago (Frontiers in Agronomy, 2020)
Potato is one of the most important legumes and constitutes a dominant portion of the global diet. Its physiological activities as well as the quantity and quality of its tubers are influenced by water stress. Herein, we evaluate the effect of several irrigation regimes on the recovery time of potato physiological activities and yield. The treatments were composed of −40 (dry) and −60 kPa (very dry) of soil matric potential (SMP) across three stress periods of 1 (1D), 3 (3D), and 7 (7D) days. A control treatment was included that considered −20 kPa of SMP during the experiment. The results showed a complete recovery of potato plants treated by applying a SMP of −40 kPa during 1 day when compared with the plant control. Although a decrease in physiological activities was observed, the potato plant was shown to consume 10% less water in this scenario. Other treatments showed yield losses, especially the treatments under 7 days, in which plants did not fully recover. Based on the results of yield loss and water stress, a water deficit index (WDI) model was proposed. WDI values >0.78 produced significant yield losses compared to the control. Therefore, the response time is a valuable measure for future research on the impacts of water stress on plants. Also, WDI is a promising index that can assist in forecasting the impact of water stress on the level of potato productivity.